GAMBARAN PERILAKU IBU RUMAH TANGGA DALAM PENGGUNAAN GARAM BERIODIUM DI DESA BANGUN I KECAMATAN PARBULUAN KABUPATEN DAIRI TAHUN 2014 - martha veronica sihombing; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTIodine Definiency Disorders (IDD) is one of serious health problem for its influences to thesurvive and quality of human resources the risk of IDD to anyone is begin since in the pregnancy up tothe adult that cause cretin, abortion for pregnant woman, stillbirth, mental retardation, growthdisorder and intelligence disorder and the famous risk is goiter that influence the living quality ofpatient.The objective of this research is to study the behavior of housewife in using iodized salt inDesa Bangun I sub-district of Parbuluan, Regency of Dairi. This research is descriptive study withcross sectional method, and technique of sampling is done proportional allocation. The number ofpopulation in this research is 424 persons and sample for 81 persons.The result of research indicates that the knowledge of mother about the using of iodized salt isin good category for 61 persons (75,3%). The attitude of respondent also in good category for 39persons (48.1%). As well as the action in enough level for 57 persons (70,4%)Based on the result it is suggested that the housewife still use iodized salt and improve theusing of iodized salt in cooking process.Keywords : Behavior of housewife, Iodized salt, IDD